Microbial Biofilms: Human T-cell Leukemia Virus Type 1 First in Line for Viral Biofilm but Far Behind Bacterial Biofilms - Maali, Yousef; Journo, Chloé; Mahieux, Renaud; Dutartre, Hélène (Frontiers in Microbiology, 2020)
Human T-cell leukemia virus type 1 (HTLV-1) is a retrovirus associated with adult T-cell leukemia (ATL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). To date, it is the unique published example of a virus able to form a biofilm at the surface of infected cells. Deeply studied in bacteria, bacterial biofilms represent multicellular assemblies of bacteria in contact with a surface and shielded by the extracellular matrix (ECM). Microbial lifestyle in biofilms, either viral or bacterial, is opposed structurally and physiologically to an isolated lifestyle, in which viruses or bacteria freely float in their environment. HTLV-1 biofilm formation is believed to be promoted by viral proteins, mainly Tax, through remodeling of the ECM of the infected cells. HTLV-1 biofilm has been linked to cell-to-cell transmission of the virus. However, in comparison to bacterial biofilms, very little is known on kinetics of viral biofilm formation or dissemination, but also on its pathophysiological roles, such as escape from immune detection or therapeutic strategies, as well as promotion of leukemogenesis. The switch between production of cell-free isolated virions and cell-associated viral biofilm, although not fully apprehended yet, remains a key step to understand HTLV-1 infection and pathogenesis.